The effect of intradetrusor botulinum neurotoxin type A on urinary NGF, TGF BETA‐1, TIMP‐2 levels in children with neurogenic detrusor overactivity due to myelodysplasia. Issue 7 (16th January 2017) - Top, Tuncay; Sekerci, Cagri Akin; Isbilen‐Basok, Banu; Tanidir, Yiloren; Tinay, Ilker; Isman, Ferruh Kemal; Akbal, Cem; Simsek, Ferruh; Tarcan, Tufan
Abstract : Aims: The aim of this study was to determine the value of urine nerve growth factor (NGF), transforming growth factor beta 1 (TGF‐Beta‐1), tissue inhibitor of matrix metalloproteinase 2 (TIMP‐2) levels to predict the urodynamic profile before and after botulinum neurotoxin type A (BoNT‐A) treatment in children with myelodysplasia. Methods: This prospective study included 15 children with myelodysplasia who underwent intradetrusor BoNT‐A injections due to neurogenic detrusor overactivity (NDOA). Urine samples of each child were collected before and after BoNT‐A injections, specifically at the first and third postoperative months. Urine samples were analyzed with ELISA method and NGF, TGF‐Beta‐1, and TIMP‐2 levels were measured. Urine marker levels and clinical findings were assessed for statistical significance with Wilcoxon Signed Ranks Test and Friedman Test. Results: A total of 15 children (5 boys and 10 girls) were assigned as the study group. Mean age of the patients was 7.1 ± 2.5 years (range 2.5‐11). A statistically significantly decline was observed in urinary TGF‐Beta‐1 and NGF levels following BoNT‐A injections, compared to the preoperative levels ( P  < 0.05). TIMP‐2 levels also tend to decrease following BoNT‐A injections but this was not statistically significant compared to the preoperative levels. Conclusion: This preliminary study, suggests urinary TGF‐Beta‐1 and NGF as a potent marker in children with NDOA, as they decline following BoNT‐A injection. Further studies are needed in identifying their special role in assessing treatment success after invasive interventions.